Comparative analysis of risk factors associated with degeneration of adjacent segments: zero-profile anchored spacer vs. anterior cervical plate and cage construct - Wu, Zhikai; Wang, Wenhao; Zhou, Feng; Xiang, Pan; Li, Yangfeng; Yang, Huilin; Chu, Genglei (Frontiers in Medicine, 2024)
Objective Anterior cervical discectomy and fusion (ACDF) is an established treatment for cervical degenerative disc disease, but cervical spine surgery may affect sagittal alignment parameters and induce adjacent segment degeneration (ASD). This study aimed to determine the risk factors for developing ASD following anterior cervical plate and cage (ACPC) compared with the use of zero-profile anchored spacer (ROI-C). Methods A retrospective contrastive study included 105 patients who underwent ACPC or ROI-C between January 2014 and October 2019 at our treatment centre. There were 50 cases in the ROI-C group and 55 patients in the ACPC group. Clinical and radiological results and the incidence of ASD were assessed after surgery. All patients were further divided into the ASD and non-ASD groups for subgroup analysis. Results At each follow-up time, there was no statistically significant in radiographic parameters between the two groups. The overall ASD rate was higher in the ACPC group than in the ROI-C group (65.5% vs. 44.0%, p = 0.027). The low preoperative Cobb angle, low preoperative segment angle (SA), and loss of Cobb (ΔCobb) were significantly correlated with ASD. However, clinical outcomes were not associated with ASD at any postoperative follow-up visit. Conclusion Equally good therapeutic effects were achieved with both the ROI-C and ACPC. The occurrence of ASD was considerably higher in the ACPC group than in the ROI-C group. The preoperative Cobb angle, preoperative SA, and ΔCobb were the most associated with an increase in the risk of ASD.